Utilization of microalgae, Chlorella sp. UMT LF2 for bioremediation of Litopenaeus vannamei culture system and harvesting using bio-flocculant, Aspergillus niger. (January 2023) - Nasir, Nurfarahana Mohd; Jusoh, Ahmad; Manan, Hidayah; Kasan, Nor Azman; Kamaruzzan, Amyra Suryatie; Wan Abdul Karim Ghani, Wan Azlina; Kurniawan, Setyo Budi; Lananan, Fathurrahman
Abstract: Microalgae are well known as autotrophic microorganisms in aquaculture wastewater treatment, however their role in the aquaculture system is rarely explored. The purpose of this study is to evaluate the influence of adding microalgae, Chlorella sp. UMT LF2, on the functionality for bioremediation and growth performance of Whiteleg shrimp, Litopenaeus vannamei in the nursery phase reared in a control culture system. Secondly, the response surface methodology (RSM) was used to investigate further on the optimal condition for the harvesting process of excess microalgae biomass using bio-flocculant from the filamentous fungus, Aspergillus niger . The experimental set-up with Chlorella sp. additions were compared to the control group without the microalgae addition based on the water quality, microalgae biomass and shrimp growth performance. Water samples were collected and underwent in-situ and ex-situ involving nine physicochemical parameters. The results showed that introducing microalgae with zero water exchange as treatment tanks reduced the NH3, NO2 − and PO4 3− during the intermediate until the two days before the 30-day culture period's end. Microalgae also enhanced shrimp survival and growth performance significantly 89% as compared to the control, 68%. Furthermore, the culture with the addition of microalgae maintained pH stability and enhanced dissolved oxygen during daytime in the culture water. Therefore, this finding confirmed that Chlorella sp. UMT LF2 addition is promising in improving rearing environment and nursery performance for L. vannamei in culture system. However, further research is required to demonstrate the harvesting by-product from the culture system and the potential applications.